DETERMINAN PROFITABILITAS PADA BPR DI JAWA TENGAH TAHUN 2012 – 2017 - Siti Khotimah, 15.05.52.0363; Masdjojo, Gregorius N (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the influence of Credit Provided, Interbank Assets, Non Performing Loans, Savings, Deposits and Capital Adequacy Ratio on Profitability of Rural Banks 2012 - 2017. This study uses purposive sampling. Based on these criteria, a sample of 28 banks was obtained with an observation period of 6 years. Because this type of data is a combination of "Cross-section" and "Time-series" data, the data analysis uses panel data regression analysis. The estimation process uses the Fixed Effect Model (FEM) and Random Effect Model (REM) methods. Selecting the best model uses the "Haussman Test". The results of data analysis are based on the recommended Haussman Test to use the REM method. The results showed that the Credit Provided, Interbank Assets and Deposits did not affect Profitability, Non Performing Loans had a significant negative effect on Profitability, Savings and Capital Adequacy Ratio had a significant positive effect on Profitability.